Pengaruh Earnings Aggresiveness Terhadap Cost of Equity Dengan Persistensi Laba Sebagai Variabel Moderating (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2014-2016) - Isma Delita; Erly Mulyani (Universitas Negeri Padang, 2018)
The research aim to examine the efect of earnings aggressiveness on cost of equity and earnings persistence as a moderation variable. Population in this research are manufactoring companies listed in Indonesia Stock Exchange(IDX) in 2014 to 2016. The sample of study of study was determined by using purposive sampling method, and that total sample 41 manufacturing companies. The data used in this research and secondary data.the technique of collecting data by the method of documentation at www.idx.co.id. The analytical method used is Moderatated Regression Analysis. The result showed earnings aggressiveness have negative significant efect on cost of equity and earnings persistence negatively moderates (weaken) the relationship between earnings aggressiveness and cost of equity.Keywords: cost of equity, earnings aggressiveness, earnings persistence